(untitled) - Bergmann, Sebastian (Indianapolis, IN, 2011)
Presents information and a variety of case studies focusing on creating sustainable applications and frameworks using PHP.
Keywords: PHP (Ngôn ngữ lập trình máy tính),PHP (Computer program language)